Prevalence, Virulence Gene Distribution and Alarming the Multidrug Resistance of Aeromonas hydrophila Associated with Disease Outbreaks in Freshwater Aquaculture - Doan Thi Nhinh; Dung Viet Le; Kim Van Van; Nguyen Thi Huong Giang; Lua Thi Dang; Truong Dinh Hoai (MDPI AG, 2021)
The study aims to evaluate the infection prevalence, virulence gene distribution and antimicrobial resistance of Aeromonas hydrophila associated in diseased outbreaks of cultured freshwater fish in Northern Vietnam. The confirmed A. hydrophila were screened for the presence of the five pitutative-virulence genes including aerolysin (aerA), hemolysin (hlyA), cytotonic enterotoxin (act), heat-labile cytotonic enterotoxin (alt), and heat-stable enterotoxin (ast), and examined the susceptibility to 16 antibiotics. A total of 236 A. hydrophila isolates were recovered and confirmed from 506 diseased fish by phenotypic tests, PCR assays, and gyrB, rpoB sequenced analyses, corresponding to the infection prevalence at 46.4%. A total of 88.9% of A. hydrophila isolates harbored at least one of the tested virulence genes. The genes aerA and act were most frequently found (80.5% and 80.1%, respectively) while the ast gene was absent in all isolates. The resistance to oxacillin, amoxicillin and vancomycin exhibited the highest frequencies (>70%), followed by erythromycin, oxytetracycline, florfenicol, and sulfamethoxazole/trimethoprim (9.3-47.2%). The multiple antibiotic resistance (MAR) index ranged between 0.13-0.88 with 74.7% of the isolates having MAR values higher than 0.2. The results present a warning for aquaculture farmers and managers in preventing the spread of A. hydrophila and minimizing antibiotic resistance of this pathogen in fish farming systems.